Rethinking Secondary Education Classroom Design to Meet E-Learning Needs in Imo State, Nigeria - Madu, Onyewuchi M. (International Journal of Educational Management, 2021)
The study focused on rethinking secondary education classroom design to meet e-learning needs in Imo State, Nigeria. Three research questions and three hypotheses guided the study. The study adopted the descriptive research design. The population of the study comprised 488 computer teachers in the 597 secondary schools in Imo State, Nigeria. Using stratified random sampling technique, a sample size of 219 was drawn representing 44.8% of the population based on the 3 Education Zones. An instrument titled “Rethinking Secondary Education Classroom Design to meet E-learning Needs Questionnaire (RSECDENQ)” structured by the researcher which was validated and with reliability index of 0.85 determined with Cronbach Alpha was used for data generation. Mean and standard deviation were used in answering research questions while z-test statistics was used to test the hypotheses at 0.05 alpha level. The study revealed among others that there are e-learning needs that necessitate the rethink of classroom design in secondary schools in Imo State. It was recommended among others that on the basis of the needs, educators, planners, designers and architects should rethink how to construct, create and organize classroom spaces to ensure e-learning in secondary schools.